Integrated multi-omics analysis reveals rumen and rectal microbiota–metabolite interaction features in polytocous fine-wool sheep with divergent residual feed intake - Kong, Menghua; Pan, Zhangyuan; Wang, Xu; Huang, Juncheng; Tulafu, Hanikezi; Xu, Yue; Sulaiman, Yiming; Wu, Weiwei (Frontiers in Microbiology, 2026)
Residual feed intake (RFI) is a key indicator of feed efficiency in ruminants. To elucidate the potential regulatory roles of microorganisms and metabolites under different RFI levels, we investigated 24 polytocous fine-wool sheep (12 high-RFI and 12 low-RFI) using metagenomic sequencing and non-targeted metabolomics of rumen and rectal contents. Significant differences in average daily feed intake, residual feed intake, and feed conversion ratio were observed between groups (p < 0.001). LEfSe analysis identified four and seventeen RFI-associated microbial biomarkers in the rumen and rectum, respectively, with s_Ruminococcus_albus and s_Ruminococcus_bicirculans as common core taxa. Functional annotation revealed that high-RFI sheep were enriched in amino acid metabolism and xenobiotic degradation pathways in the rumen, whereas low-RFI sheep were enriched in pathways related to development and regeneration. In the rectum, high-RFI sheep showed enrichment in protein folding and degradation, carbohydrate metabolism, and energy metabolism, while low-RFI sheep were enriched in transcriptional regulation and signal transduction pathways. Metabolomic analysis detected 297 and 1,130 differential metabolites in the rumen and rectum, respectively, mainly lipids, organic acids, and derivatives. KEGG enrichment indicated that rumen metabolites were primarily involved in bile acid biosynthesis and riboflavin metabolism, while rectal metabolites were enriched in energy metabolism and multiple amino acid pathways, including arachidonic acid, tryptophan, tyrosine, lysine, and methionine metabolism. Integrated analysis revealed significant associations between key bacterial taxa and metabolites, and network construction identified core nodes potentially engaged in synergistic regulation, providing insights into their roles in RFI phenotype formation. Collectively, these findings highlight the distinct contributions of the rumen and rectum to feed efficiency in sheep and offer theoretical support for nutritional regulation strategies to improve ruminant production performance.